Polish Higher-Education Institutions in International Cooperation: Evidence from the European Union Framework Programmes - Krzyżek-Liburska, Sylwia (Journal of Public Governance, 2023)
Objective: Polish higher-education institutions (HEIs) compete for European funds with excellent European universities that have comprehensive support systems for applying for research grants. This paper’s aim is to analyse the patterns of participation of Polish higher-education institutions in the 7th and 8th EU framework programmes, and their relationship with the characteristics of universities and national and geographical effects.Research Design & Methods: This article uses the CORDIS database for analysing data concerning projects financed under FP7 and the Horizon 2020 Programme.Findings: The literature emphasises the weak starting position of Polish entities in competing for international grants. The low results of Polish institutions in EU FPs might be due to many factors, including system and structural, institutional, and mental barriers.Implications / Recommendations: There is the necessity for a detailed examination of the determinants of the success of research proposals and the development of a system that will support strategic decisions on applying for grants at Polish universities in order to increase the absorption of EU funds.Contribution / Value Added: New legislation in Poland has forced universities to change their expectations towards academic staff in order to achieve the highest possible categorisation of disciplines and universities. Polish scientists are under pressure to publish their research in reputable journals. Therefore, it might be possible to observe a direct emphasis on application for research grants and timely settlement of projects in case of obtaining grants.